An exploration of Canadian identity in recent literary narratives of the Franklin expeditions - Kennedy, Victor (ELOPE (Ljubljana), 2006)
Sir John Franklin's three expeditions to the high Arctic in 1819, 1825, and 1845 have become the stuff of Canadian legend, enshrined in history books, songs, short stories, novels, and web sites. Franklin set out in 1845 to discover the Northwest Pass age with the most advanced technology the British Empire could muster, and disappeared forever. Many rescue explorations found only scant evidence of the Expedition, and the mystery was finally solved only recently. This paper will explore four recent fictional works on Franklin's expeditions, Stan Rogers' song "Northwest Passage", Margaret Atwood's short story "The Age of Lead", Rudy Wiebe's A Discovery of Strangers, and John Wilson's North with Franklin: the Lost Journals of James Fitzjames, to see how Franklin's ghost has haunted the hopes and values of nineteenth-century, as well as modern, Canada.
Keywords: Franklinova odprava; kanadska književnost; kanadska kultura; literarne upodobitve; odprave